2013
DOI: 10.1021/cs400069z
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Hydrotreating of Pyrolysis Bio-Oil and Its Oxygen-Containing Model Compounds

Abstract: Considerable worldwide interest exists in discovering renewable energy sources that can substitute for fossil fuels. Lignocellulosic biomass, the most abundant and inexpensive renewable feedstock on the planet, has a great potential for sustainable production of fuels, chemicals, and carbon-based materials. Fast pyrolysis integrated with hydrotreating, one of the simplest, most cost-effective, and most efficient processes to convert lignocellulosic biomass to liquid hydrocarbon fuels for transportation, has at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
488
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 615 publications
(505 citation statements)
references
References 158 publications
5
488
0
5
Order By: Relevance
“…Accordingly, the extent of hydrogen incorporation in these fixed bed systems will be limited by thermodynamic equilibrium, with greater hydrogen incorporation achieved in fixed bed reactor #2 due to its lower operating temperature. The lower operating pressure of the ex situ upgrading reactors, chosen to maintain the pyrolysis products in the vapor phase, will also limit the extent of hydrogenation, as compared to typical hydrotreating conditions (50-100 bar) [17,18]. Deoxygenation can be achieved through decarbonylation (removal of oxygen as CO), decarboxylation (removal of oxygen as CO 2 ), hydrodeoxygenation (encompassing both direct hydrogenolysis and hydrogenation-dehydration; removal of oxygen as H 2 O), and certain C-C coupling reactions (discussed below) [12,17,18].…”
Section: Reaction Chemistry and Catalyst Optionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, the extent of hydrogen incorporation in these fixed bed systems will be limited by thermodynamic equilibrium, with greater hydrogen incorporation achieved in fixed bed reactor #2 due to its lower operating temperature. The lower operating pressure of the ex situ upgrading reactors, chosen to maintain the pyrolysis products in the vapor phase, will also limit the extent of hydrogenation, as compared to typical hydrotreating conditions (50-100 bar) [17,18]. Deoxygenation can be achieved through decarbonylation (removal of oxygen as CO), decarboxylation (removal of oxygen as CO 2 ), hydrodeoxygenation (encompassing both direct hydrogenolysis and hydrogenation-dehydration; removal of oxygen as H 2 O), and certain C-C coupling reactions (discussed below) [12,17,18].…”
Section: Reaction Chemistry and Catalyst Optionsmentioning
confidence: 99%
“…The lower operating pressure of the ex situ upgrading reactors, chosen to maintain the pyrolysis products in the vapor phase, will also limit the extent of hydrogenation, as compared to typical hydrotreating conditions (50-100 bar) [17,18]. Deoxygenation can be achieved through decarbonylation (removal of oxygen as CO), decarboxylation (removal of oxygen as CO 2 ), hydrodeoxygenation (encompassing both direct hydrogenolysis and hydrogenation-dehydration; removal of oxygen as H 2 O), and certain C-C coupling reactions (discussed below) [12,17,18]. Decarbonylation and decarboxylation proceed through cleavage of C-C bonds, thus reducing oxygen content at the expense of carbon efficiency, with decarboxylation being preferred as two oxygen atoms are removed per carbon atom.…”
Section: Reaction Chemistry and Catalyst Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…have differing rates, and different catalysts will promote DDO or HYD as a primary reaction depending on the nature of the metal and the support [10]. It has been observed that noble metals favor HYD whereas sulfided catalysts preferentially undergo DDO reactions [23], [24]. In addition to facilitating multiple reactions, an ideal bifunctional catalyst should still be able to exhibit a high turnover frequency (TOF) and the capability to maintain this activity after repeated trials.…”
Section: Bifunctional Catalysismentioning
confidence: 99%